PENGARUH SHARIAH PRINCIPLES ADHERENCE, RELATIONSHIP MARKETING, DAN SERVICE QUALITY TERHADAP CUSTOMER LOYALTY PADA LEMBAGA KEUANGAN SYARIAH - Wiwoho, Gunarso (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
This study aims to analyze the effect of shariah principles adherence, relationship marketing, service quality on customer loyalty in Alfa Nusa Barru Kebumen KSPPS members. The independent variables in this study are shariah principles of adherence, relationship marketing, and service quality, while the dependent variable is customer loyalty. The technique of collecting data using a questionnaire using a positive sampling technique, the sample in this study was a member of KSPPS Alfa Nusa Barru who had been more than three years with 100 respondents. The hypothesis was tested with the help of the SPSS 23.00 for windows program. The method used in this study is a quantitative method using multiple regression analysis. The test results show that the Shariah principles adherence has no effect on customer loyalty, relationship marketing has a positive effect on customer loyalty, and service quality has a positive effect on customer loyalty.